A Survey On The Susceptibility Of PUFs To Invasive, Semi-Invasive And Noninvasive Attacks Challenges And Opportunities For Future Directions - Mispan, Mohd Syafiq; Halak, Basel; Zwolinski, Mark (World Scientific, 2021)
Physical Unclonable Functions (PUFs) are considered to be a promising technology that provides a hardware root-of-trust for integrated circuit (IC) applications. PUFs exploit the intrinsic process variations that map a set of challenges to a set of responses. The intrinsic process variations are caused by uncontrollable deviations in the IC manufacturing process, which are unique and random from die to die and wafer to wafer. As the PUF output is device-speci¯c, PUFs can, therefore, be used in IC identi¯cation and authentication, and cryptographic key generation. Nevertheless, many di®erent successful attack techniques have already revealed vulnerabilities in certain PUFs, including invasive, semi-invasive and noninvasive attacks. In this work, we survey some of the known attacks on PUFs. We also survey the countermeasures to these types of attack presented in recent literature, and ¯nally, discuss the future challenges. Through this survey, the susceptibility of PUFs to attacks is highlighted and this information may be used to improve the quality of future PUF-based application designs